Strategi China Dalam Melindungi Keamanan Nasionalnya di Wilayah Sengketa Laut China Selatan - Kinanti Rizsa Sabilla; Ismah Rustam; Ahmad Mubarak Munir (The Department of International Relations Universitas Mataram, 2022)
This research aims to look at China's strategy for securing its national interests in the disputed South China Sea area. The concept of national power and national interest was utilized in this research, along with descriptive exploratory research methods assisted by concepts. Qualitative and literature studies have been used as data collection methods. This study aims to show that China's sincerity in asserting claims over the disputed South China Sea is not an ordinary claim. The claim action is a serious action to protect the country's national interests in both national security as well as the economy. This is due to China's belief that the South China Sea is an existing part of its territory based on ancient Chinese shipping maps, which will be maintained along with the acquisition of rights to the nine-dash line based on traditional maps. This study reveals that China's strategy is to use national power, both military and latent power